Intraoperative diagnosis of «sentinel lymph nodes» with objective to select the surgical procedure in gastric and uterus cancers - R. P. Nikitenko; V. V. Grubnik; I. Z. Gladchuk; O. M. Stepanovichus (Клінічна хірургія)
Intraoperative diagnosis of «sentinel lymph nodes» with objective to select the surgical procedure in gastric and uterus cancers